Fenomena Kenakalan Santri: Pendekatan Etnografi di Pondok Pesantren Baitul Ilmi wal Quran - Muhammad Chasbullah (Universitas Sebelas Maret, 2025)
Santri delinquency in pesantren is an intriguing issue as it challenges the common perception of pesantren as institutions fostering noble character. This phenomenon impacts not only the individual santri but also the social dynamics within the pesantren. This study investigates santri delinquency at Pondok Pesantren Baitul Ilmi wal Quran, Sidoarjo, using an ethnographic approach to delve into the experiences, interactions, and perceptions of santri regarding factors influencing their behavior. Findings reveal two primary causes of delinquency: internal and external factors. Internal factors include boredom with daily routines, lack of motivation, and difficulty adapting to pesantren values. External factors involve peer pressure, excessively strict or lenient rules, and strained relationships between santri and pesantren supervisors or administrators. Efforts to address this issue focus on individual counseling, character development, and collaboration between pesantren and santri families. This research sheds light on the social dynamics of pesantren and emphasizes the need for more empathetic management and guidance of santri. By understanding the root causes of delinquency, pesantren can adopt more effective strategies to nurture a positive and supportive environment that aligns with their mission of moral and spiritual development.